2018
DOI: 10.3390/colloids2040058
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Bioemulsifier-Producing Bacillus subtilis UCP 0146 Isolated from Mangrove Sediments

Abstract: In this work, we investigated the potential of Bacillus subtilis UCP 0146 in the bioconversion of a medium containing 100% cassava flour wastewater to obtain a bioemulsifier. The evaluation of the production was carried out by the emulsification index (IE24) and the surface tension (ST). The ionic charge, stability (temperature, salinity, and pH measured by IE24 and viscosity), and ability to remove and disperse oil and textile dye were investigated. B. subtilis produced an anionic bioemulsifier in the medium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…The result obtained in relation to the yield of isolated biomolecule corroborates the data found in the literature. These describe yields for bioemulsifiers of microbiological origin between 0.1 and 3.15 g/L [25,30,[37][38][39]. The yield of the fungal bioemulsifier of this study was superior to the bacterial of Lactobacillus plantarum, obtaining only 0.7 g/L of the isolate [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result obtained in relation to the yield of isolated biomolecule corroborates the data found in the literature. These describe yields for bioemulsifiers of microbiological origin between 0.1 and 3.15 g/L [25,30,[37][38][39]. The yield of the fungal bioemulsifier of this study was superior to the bacterial of Lactobacillus plantarum, obtaining only 0.7 g/L of the isolate [39].…”
Section: Discussionmentioning
confidence: 99%
“…[19]. A recent study selected several cultivation aspects to investigate bioemulsifier production by Bacillus subtilis grown in cassava wastewater, and found that only inoculum size was statistically significant in biomolecule production [25].…”
Section: Discussionmentioning
confidence: 99%
“…Cell-free metabolic liquid was submitted separately at different temperatures (0, 5, 30, 37, 50, and 100°C), adjusted to different pH values (2, 4, 6, 8, 10, and 12) or NaCl (2, 4, 6, 8, 10, and 12%). en, EI 24 was determined using burned motor oil as a hydrophobic substrate following the methodology previously described in Section 2.4.4 [25,26].…”
Section: Determination Of the Stability Of The Bioemulsifiermentioning
confidence: 99%
“…e effect of the bioemulsifier produced by S. maltophilia UCP 1601 on the viscosity of hydrophobic compounds (WSO and burned motor oil) was investigated using the methodology described by Andrade Silva et al [27] and Maia et al [26]. e viscosity of the hydrophobic compounds was determined in test tubes before and after adding 2 ml of the cell-free metabolic liquid (crude bioemulsifier) of the selected condition of the FFD, and the mixture was vigorously homogenized in vortex for 1 min.…”
Section: Effect Of the Bioemulsifier On The Viscosity Of Hydrophobicmentioning
confidence: 99%
See 1 more Smart Citation